EFEKTIVITAS KOMPRES BULI-BULI DALAM MENURUNKAN NYERI AKUT PADA PASIEN CROHN'S DISEASE DI RSUP DR. SARDJITTO YOGYAKARTA - Arta Damayanti; Armenia Diahsari; Dwi Prasetyorini (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Crohn's disease is a chronic inflammatory disease of the gastrointestinal tract that can cause various symptoms, one of which is acute abdominal pain. Untreated pain can affect the patient’s physical and psychological condition and interfere with sleep patterns and daily activities. The aim of this case study is to describe nursing care in a patient with Crohn's disease experiencing acute pain and timplementation of a non-pharmacological intervention in the form of warm compresses using a hot water bag. Warm compresses using a hot water bag are a process of heat transfer into the body, which can increase tissue perfusion and promote muscle relaxation, thereby reducing or relieving abdominal pain. Warm compresses also provide comfort, reduce pain intensity, and help relax the muscles in the affected area.The method used in this study was a case study with a nursing process approach in a pediatric patient treated at Aster Timur Ward, Dr. Sardjito General Hospital, Yogyakarta. Data were collected through interviews, observation, and physical examination.The results showed that the patient experienced abdominal pain with a score of 7 on the Numeric Rating Scale (NRS). After the application of warm compresses, the pain decreased to a score of 5 on the Numeric Rating Scale (NRS), and the patient appeared more relaxed and no longer grimacing.